Novel Quinoline- and Naphthalene-Incorporated Hydrazineylidene–Propenamide Analogues as Antidiabetic Agents: Design, Synthesis, and Computational Studies - Osama Alharbi; Wael H. Alsaedi; Mosa Alsehli; Saif H. Althagafi; Hussam Y. Alharbi; Yazeed M. Asiri; Ramith Ramu; Mohammed Al-Ghorbani (Pharmaceuticals)
Background: Type 2 diabetes has become a significant global health challenge. Numerous drugs have been developed to treat the condition, either as standalone therapies or in combination when glycemic control cannot be achieved with a single medication. As existing treatments often come with limitations, there is an increasing focus on creating novel therapeutic agents that offer greater efficacy and fewer side effects to better address this widespread issue. Methods: The methylene derivatives 3a,b were coupled with phenyl/ethyl isothiocyanate in the basic medium, and dimethyl sulfate was subsequently added. Further, 5a–d were reacted with the quinoline/naphthalene hydrazides 6a,b. The target compounds 7a–g were subjected to the in vitro enzyme inhibition studies on α-glucosidase, α-amylase, and aldose reductase. Results: 7g exerted remarkable inhibitory effects on α-glycosidase [Inhibitory Concentration (IC50): 20.23 ± 1.10 µg/mL] and α-amylase (17.15 ± 0.30 µg/mL), outperforming acarbose (28.12 ± 0.20 µg/mL for α-glycosidase and 25.42 ± 0.10 µg/mL for α-amylase), and exhibited a strong inhibition action on aldose reductase (12.15 ± 0.24 µg/mL), surpassing quercetin (15.45 ± 0.32 µg/mL) and the other tested compounds. In a computational study, 7g demonstrated promising binding affinities (−8.80, −8.91 kcal/mol) with α-glycosidase and α-amylase, compared to acarbose (−10.87, −10.38 kcal/mol) for α-glycosidase and α-amylase. Additionally, 7g had strong binding with aldose reductase (−9.20 kcal/mol) in comparison to quercetin (−9.95 kcal/mol). Molecular dynamics (MDs) simulations demonstrated that 7g remained stable over a 100 ns simulation period, and the binding free energy estimates remained consistent throughout this time. Conclusions: We reported the modification of quinoline and naphthalene rings to hydrazineylidene–propenamides 7a–g using various synthetic approaches. 7g emerged as a leading candidate, exhibiting greater inhibition of α-glycosidase, α-amylase, and aldose reductase. These findings underscore their potential as essential molecules for the development of innovative antidiabetic treatments.